2011
DOI: 10.1666/10-131.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the species Stephanomys progressus, a murid (Rodentia) from the early Pleistocene of Spain

Abstract: The genus Stephanomys (Muridae, Rodentia) is one of the most common elements in the late Miocene to Early Pleistocene mammal faunas from the Ibero-Occitan region. Its geographic distribution is limited to this area with only two mentions in the late Miocene of Italy (de Giuli, 1989) and Algeria (Coiffait et al., 1985). The genus has been subject of numerous studies, some of them suggesting different interpretations on the phylogenetic relationships between the various described species (Gmelig-Meyling and Mich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The molars of Stephanomys progressus are slightly larger than those from Pedrera del Corral d'en Bruach. In addition, the M2 of S. progressus shows a clearly lessdeveloped t9 than the studied M2 does (Cordy 1976;Minwer-Barakat et al 2011). The Moreover, the large size ( as S. progressus.…”
Section: Genus Eliomys Wagner 1849mentioning
confidence: 70%
See 3 more Smart Citations
“…The molars of Stephanomys progressus are slightly larger than those from Pedrera del Corral d'en Bruach. In addition, the M2 of S. progressus shows a clearly lessdeveloped t9 than the studied M2 does (Cordy 1976;Minwer-Barakat et al 2011). The Moreover, the large size ( as S. progressus.…”
Section: Genus Eliomys Wagner 1849mentioning
confidence: 70%
“…We have revised some specimens of Stephanomys from Almenara-Casablanca 1 stored at the Institut de Paleoecologia Humana i Evolució Social (Tarragona, Spain) in order to clarify their determination. We have found that this material fits better with S. balcellsi than with S. progressus, as all the available M2s develop a t9, a diagnostic character that differentiates S. balcellsi from S. progressus (see Minwer-Barakat et al 2011). There is therefore an inconsistency in the identification of the descendant of S. balcellsi in the older site of Almenara-Casablanca 4.…”
Section: Genus Eliomys Wagner 1849mentioning
confidence: 82%
See 2 more Smart Citations
“…However, some slight differences exist between S. dubari and S. numidicus , such as the occasional presence of an anterocentral cuspid (tma) in M 1 of S. numidicus (67% in the type population from Argoub Kemellal 1) and the size of M 2 and M 2 , which are slightly larger in S. numidicus . The Stephanomys lineage shows morphological and biometrical changes throughout the late Miocene, Pliocene and early Pleistocene, including an increase in size, an increase in crown height and better development of longitudinal connections in both upper and lower molars (Minwer‐Barakat et al ., , ). The transition between S. ramblensis and S. dubari can be recognized in the Granada Basin (García‐Alix et al ., ), where an increase in both size and height of the longitudinal connections can be seen in teeth from older to more recent sites.…”
Section: Discussionmentioning
confidence: 99%